What were residents' petitions in Beijing: Based on text mining - Zhong Wang; Ying Zhong (Journal of Urban Management, 2020)
Understanding the petition of citizens is the basis for improving urban governance and citizen satisfaction during urbanization. Given Beijing's rapid growth and large scale in urbanization, it represents an interesting case study to explore the petitions of citizens. In this paper, we analyze nearly five thousand petitions through automated text analysis in order to summarize and explore the prevalent concerns voiced by Beijing citizens. We found that citizens' petition issues are regarding household registration (30.3%), illegal construction (22.6%), education (13.4%), demolition (11.8%), city management (9.8%), housing (7.7%), and traffic (4.4%). Petition Network Platform in Chinese cities has accumulated information resources, but the development and utilization is lagging behind. Text Mining of the public letters has been intricate; yet, it may serve as a novel technique to analyze and improve urban governance in China. The public should be encouraged to express their demands through the network platform for enriching information resources. Moreover, the response mechanism should be established for the public opinions derived from Text Mining, to improve public satisfaction.
Keywords: 710; Petitions; Urban residents; Network platform; Interaction between government and public; Text mining; Case study